Methods of the Verification of the Expert’s Opinion within Criminal Procedure of Ukraine - B. V. Shabarovskyi (Law and Safety)
Considering the fact that the verification of evidence remains poorly researched criminal procedural phenomenon and the expert’s opinion is an important mean of establishing the circumstances of criminal proceedings, the purpose of this study is to distinguish and analyze the methods of verifying the expert’s opinion within criminal procedure of Ukraine.